Evaluation of the role of family support as an educator, monitor, and motivator in improving OSH practices in the informal sector in Gunungkidul, Yogyakarta - Hartono; Sumardiyono; Sukismanto, Sukismanto; Andayani, Tri Rejeki; Fitriana, Lala Budi; Nugroho, Ariyanto (Journal of Health Education, 2024)
Background: Continuous education, training, and monitoring are the keys to success in increasing Occupational safety and Heallth (OSH) knowledge, attitudes, and practices, so evaluation of treatment is necessary  Methods: This research method uses a pre-test post-test group design with control, The research population is limestone workers in Gunungkidul Regency, Daerah Istimewa Yogyakarta, with a population of 32 limestone processing groups taken as research samples using purposive sampling so that 90 research respondents are obtained. divided into four research and control groups. Treatment for 1 month and evaluation carried out after more than three months after the treatment was completed. Data were analyzed using the Kruskal-Wallis test (α : 0.05) and continued with the pairwise comparison test. Results: The evaluation results show that there are differences in all treatments, with the result that family support (FS) has an influence on changes in OSH knowledge and attitudes when compared to peer support (PS) and controls and still has the same effect when compared to a combination of FS and PS. Conclusions: The conclusion is that FS has a good effect on increasing OSH knowledge, attitudes, and practices, and it is suggested for further research related to the role of PS for workers.